Deciphering the immunocellular regulatory network in inflammatory bowel disease: from susceptibility genes to cellular effectors and toward precision therapies - Wu, Zhuzhu; Wang, Xiaolin; Guan, Zitong; Han, Mengxue; Ma, Wenke; Li, Jie; Man, Shuai; Wang, Zhenguo; Wu, Qibiao (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD) is a chronic, immune-mediated intestinal disorder driven by dysregulated immune responses in genetically susceptible individuals. Despite recent advances in treatment, more than 30% of patients either fail to respond initially or lose response over time, underscoring the need for a deeper mechanistic understanding of immunogenetic pathways and the development of individualized therapeutic strategies. We first discuss how newly identified susceptibility genes (e.g., IL23R, NOD2, BDNF, SLC) and their polymorphisms influence immune cell function and epithelial barrier integrity. Single-cell technologies have further revealed novel cell subsets and interactions underlying disease heterogeneity. We then explore the clinical efficacy of classical and emerging targeted therapies, including cytokine-specific biologics, JAK inhibitors, and novel strategies aimed at restoring regulatory T-cell function or blocking integrin-mediated lymphocyte trafficking. Additionally, we highlight promising therapeutic approaches such as fecal microbiota transplantation, microbial metabolite-based interventions, and nanotherapeutics. We further discuss how genetic insights and immune biomarkers can facilitate treatment personalization and improve prognostic stratification. Ultimately, this review emphasizes the transition from broad immunosuppression to precision medicine and proposes integrated approaches—combining multiomics profiling, immune monitoring, and novel therapeutics—to achieve sustained remission and improve long-term outcomes in IBD patients.